Dietary sources of polyphenols in the Mediterranean healthy Eating, Aging and Lifestyle (MEAL) study cohort. (18th August 2017) - Godos, Justyna; Marventano, Stefano; Mistretta, Antonio; Galvano, Fabio; Grosso, Giuseppe
Abstract: The aim of this study was to estimate the dietary intake and major food sources of polyphenols in the Mediterranean healthy Eating, Aging and Lifestyles (MEAL) study cohort. A total of 1937 individuals (18 + y) of urban population of Catania, Italy, completed a validated 110-item food frequency questionnaire; Phenol-Explorer database was used to estimate polyphenol intake. Mean intake of polyphenols was 663.7 mg/d; the most abundant classes were phenolic acids (362.7 mg/d) and flavonoids (258.7 mg/d). The main dietary sources of total polyphenols were nuts, followed by tea and coffee as source of flavanols and hydroxycinnamic acids, respectively, fruits (i.e. cherries were sources of anthocyanins and citrus fruits of flavanones) and vegetables (i.e. artichokes and olives were sources of flavones and spinach and beans of flavonols); chocolate, red wine and pasta contributed to flavanols and tyrosols, respectively. These findings will be useful to assess the potential benefits of foods with high polyphenol content.